Fragmentation and Translocation Distort the Genetic Landscape of Ungulates: Red Deer in the Netherlands - de Jong, Joost F.; van Hooft, Pim; Megens, Hendrik-Jan; Crooijmans, Richard P. M. A.; de Groot, Gerard Arjen; Pemberton, Josephine M.; Huisman, Jisca; Bartoš, Luděk; Iacolina, Laura; van Wieren, Sip E.; Ydenberg, Ronald C.; Prins, Herbert H. T. (Frontiers in Ecology and Evolution, 2020)
At present, many ungulate populations have a complex history of isolation and translocation. Consequently, ungulate populations may have experienced substantial reductions of the level of overall gene flow, yet simultaneously have augmented levels of long-distance gene flow. To investigate the effect of this dual anthropogenic impact on the genetic landscape of ungulates, we genotyped 35K SNPs in 47 red deer (Cervus elaphus) of The Netherlands, including putative autochthonous relic populations as well as allochthonous populations established in private estates and rewilding areas. We applied FST and ordination analyses to determine the meta-population genetic structure and thereby the occurrence of hybridization. At population level, we investigated levels of inbreeding through individual-based diversity measures, including Runs of Homozygosity. We found that both spatial genetic structure and within-population genetic variation differed markedly from patterns assumed from present-day abundance and distribution. Notwithstanding the small spatial scale, red deer populations formed distinct genetic clusters, and some had higher genetic similarity to distant than to nearby populations. Moreover, the putative autochthonous relic deer populations had much reduced levels of polymorphism and multi-locus heterozygosity, despite relatively large current population size. Accordingly, genomes of these deer contained a high proportion of long (>5Mb) Runs of Homozygosity. Whereas the observed high levels of inbreeding warrant defragmentation measures, the presence of adjacent autochthonous and allochthonous genetic stocks imply that facilitation of geneflow would cause genetic homogenization. Such distortions of the genetic landscape of ungulates creates management dilemmas that cannot be properly anticipated without baseline genetic monitoring.